2014
DOI: 10.12741/ebrasilis.v7i1.365
|View full text |Cite
|
Sign up to set email alerts
|

Biologia de Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) em Algodoeiro de Fibra Colorida Tratado com Silício

Abstract: A lagarta Spodoptera frugiperda (Smith) é praga-chave da cultura do milho e a cada ano sua ocorrência na cultura algodoeira têm aumentado, causando danos severos desde a fase de plântula até a maturação. Objetivou-se com este trabalho avaliar o efeito do silício na biologia de S. frugiperda em algodoeiro de fibra branca e colorida. Os bioensaios foram conduzidos com duas cultivares de algodão, a BRS Cedro (fibras brancas) e BRS Verde (fibras verdes), com e sem aplicação de silício. O silício foi aplicado como … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Insect fecundity is one of the biological parameters most affected by Si. Silva et al [ 38 ] reported that male-female pairs of fall armyworm derived from larvae fed on cotton leaves treated with Si produced fewer eggs per female. At the same time, He et al [ 39 ] demonstrated that feeding with rice plants treated with Si solution significantly reduced the fecundity of Nilaparvata lugens (Stal).…”
Section: Discussionmentioning
confidence: 99%
“…Insect fecundity is one of the biological parameters most affected by Si. Silva et al [ 38 ] reported that male-female pairs of fall armyworm derived from larvae fed on cotton leaves treated with Si produced fewer eggs per female. At the same time, He et al [ 39 ] demonstrated that feeding with rice plants treated with Si solution significantly reduced the fecundity of Nilaparvata lugens (Stal).…”
Section: Discussionmentioning
confidence: 99%
“…Silva et al . (2014) reported that male–female pairs of S. frugiperda derived from larvae fed on cotton leaves treated with silicon produced fewer eggs per female, while He et al . (2015) demonstrated that feeding with rice plants treated with silicon solution significantly reduced the fecundity of Nilaparvata lugens (Stål).…”
Section: Discussionmentioning
confidence: 99%
“…These results corroborate with studies conducted by Nascimento et al (2018), which showed reduced viability and numbers of eggs of S frugiperda females fed with silicon treated plants applied both by leaf and soil. Silva et al (2014) observed that the application of silicon in cotton promoted a reduction in the production of eggs / female of S. frugiperda. ASM acts as an activator of the plant's natural defenses against pests and diseases (Tomquelski et al, 2007).…”
Section: Biological Aspects Of S Frugiperdamentioning
confidence: 99%